2020
DOI: 10.3390/w12041114
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Climate Change’s Effect on Flood Risk. Case Study of Reinosa in the Ebro River Basin

Abstract: Floods are one of the natural hazards that could be most affected by climate change, causing great economic damage and casualties in the world. On December 2019 in Reinosa (Cantabria, Spain), took place one of the worst floods in memory. Implementation of DIRECTIVE 2007/60/EC for the assessment and management of flood risks in Spain enabled the detection of this river basin with a potential significant flood risk via a preliminary flood risk assessment, and flood hazard and flood risk maps were developed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…The motivation for using the ANA-MRI-CGCM3-rcp85 model results is twofold: (i) previous experience [4]; and (ii) current validation (Figure 2). Previous experience refers to a previous work carried out by the authors [4], where the analyses showed that this climate model achieved a good fit with real annual-average daily-flow-rates.…”
Section: Selection Of the Climate Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…The motivation for using the ANA-MRI-CGCM3-rcp85 model results is twofold: (i) previous experience [4]; and (ii) current validation (Figure 2). Previous experience refers to a previous work carried out by the authors [4], where the analyses showed that this climate model achieved a good fit with real annual-average daily-flow-rates.…”
Section: Selection Of the Climate Modelmentioning
confidence: 99%
“…The motivation for using the ANA-MRI-CGCM3-rcp85 model results is twofold: (i) previous experience [4]; and (ii) current validation (Figure 2). Previous experience refers to a previous work carried out by the authors [4], where the analyses showed that this climate model achieved a good fit with real annual-average daily-flow-rates. Besides, before using the model again for this study, the authors checked and demonstrated, for the particular case of the Arga river basin (see Figure 2), that the validity of the ANA-MRI-CGCM3-rcp85 model predictions still stands.…”
Section: Selection Of the Climate Modelmentioning
confidence: 99%
See 3 more Smart Citations